A film-based fluorescent device for vapor phase detection of acetone and related peroxide explosives. (30th April 2019) - Qi, Yanyu; Xu, Wenjun; Ding, Nannan; Chang, Xingmao; Shang, Congdi; Peng, Haonan; Liu, Taihong; Fang, Yu
Abstract : A film-based fluorescent device for vapor phase detection of acetone and TATP and DADP at room temperature is reported. Abstract : On site, sensitive and selective detection of acetone vapor at room temperature is of great importance for health, and in particular for in air detection of triacetone triperoxide (TATP) and diacetone diperoxide (DADP), two improvised explosives commonly used by terrorists in suicide attacks. This paper reports a relevant high-performance film-based fluorescent device, where a newly synthesized perylene monoimide modified non-planar organoboron derivative (PMI-BQ) was adopted as the sensing fluorophore. The performance of the device is excellent as evidenced by less than 2 s response time, no more than 10 s recovery time, nearly perfect reversibility, and lower than 50 ppm experimental detection limit (DL) for acetone. In addition, the presence of potential interferences showed little effect upon the sensing. Notably, more than 30 days sensing tests showed no observable degradation in the performance of the film device. Further tests revealed that the film-based device can be further used for the detection of TATP and DADP. The experimental DLs for the two explosives are lower than 30 and 50 μg, respectively. The superior performance of the device was ascribed to the non-planar structure of the sensing fluorophore as it may produce micro-channels in the film. Meanwhile, solvation may also play a crucial role in the process. We believe our contribution not only realizes reversible fluorescence sensing of acetone vapor and the related explosives, but also demonstrates that the combination of solvent effect and non-planar structure could be an effective way to develop high performance fluorescent sensing films.